Pengenalan dan Pemanfaatan Biofertilizer Bakteri Indigenus dari Tanah Gambut Bagi Siswa SMK Negeri 1 Rasau Jaya Kubu Raya Kalimantan Barat - Siti Khotimah; Dwi Gusmalawati; Rafdinal Rafdinal; Irwan Lovadi; Firman Saputra; Muhammad Fajar (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2024)
Biofertilisers are biofertilisers that contain functional microorganisms that can provide or increase nutrient availability for plants. However, understanding and making biofertilisers requires knowledge and skills to produce good biofertilisers. This training was conducted to increase knowledge and skills about biofertilisers for students of SMK Negeri 1 Rasau Jaya Kubu Raya. The method of implementing this activity includes preparation (Activity plan), implementation (Delivery of material) and evaluation (Filling out questionnaires). This activity was carried out at Talita Garden Rasau Jaya III Rasau Jaya Kubu Raya which was attended by 16 participants. The material about biofertilisers was delivered directly by the resource person. Based on the evaluation through the questionnaire sheet, this training was able to increase the participants' knowledge and skills about biofertilisers from 81.25% not knowing to 40.00% knowing and 60.00% very knowing. This training was very useful (68.75%) and inspiring (100%). Based on the knowledge of biofertilisers that have been obtained, participants hope to practice at school and at home.